A Case of Newcastle Disease Virus in Red-Headed Lovebird in Sudan - Egbal Sidahmed Abdelrahim; Jedda Elhag (Case Reports in Veterinary Medicine)
Two diseased red-headed lovebirds were presented for diagnosis to the Department of Avian Diseases and Diagnosis, Veterinary Research Institute, aged 37 days and 4 years. The symptoms were dyspnea, cyanosis of the comb, diarrhea, and fever. Postmortem lesions included pale liver and bloody enteritis. Newcastle disease virus was isolated from lungs, trachea, and intestines following inoculation in the allantoic cavity of 10-day-old fertile eggs; the NDV was identified by the means of HA&HI tests using specific NDV antisera (Lasota strain). The isolate agglutinated equine RBCs but failed to agglutinate sheep and bovine RBCs. The pathogenicity of the NDV isolate was studied, the mean death time was 96 hours, and the intracerebral pathogenicity index (ICPI) value was 0.9, indicating the isolate of lentogenic type.